2020
DOI: 10.22219/jes.v6i1.14993
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Zakah, Islamic Financing, Sukuk and Inflation on National Economic Growth with Poverty as a Moderation Variable

Abstract: The aims of this study is to analyze the influence of zakah, Islamic financing, sukuk and inflation on national economic growth with poverty variable as a moderating variable. This study is quantitative uses secondary data types with the panel data model, namely quartly data from the variable zakah, Islamic financing, sukuk, inflation, poverty, and economic growth in Indonesia period 2014-2018. The  data  collected through annual report and official report and tested using  moderated regression  analysis  (MRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…Using generalized method of moments analysis, the researchers found that macroeconomic stability, particularly GDP per capita, had a significant influence on the development of Sukuk, thereby supporting the demand-following hypothesis. In contrast, Marsi and Wardani (2020) and Ridlo et al (2021) confirmed that Sukuk is an insignificant factor in influencing Indonesian's economic growth. Thus, they certainly verified neutrality hypothesis.…”
Section: Islamic Bond and Economic Growthmentioning
confidence: 85%
“…Using generalized method of moments analysis, the researchers found that macroeconomic stability, particularly GDP per capita, had a significant influence on the development of Sukuk, thereby supporting the demand-following hypothesis. In contrast, Marsi and Wardani (2020) and Ridlo et al (2021) confirmed that Sukuk is an insignificant factor in influencing Indonesian's economic growth. Thus, they certainly verified neutrality hypothesis.…”
Section: Islamic Bond and Economic Growthmentioning
confidence: 85%
“…With the distribution of the ZIS funds, the Muslim community who cannot afford it can still meet their needs so that consumption activity which is an indicator of economic growth, continues (Jedidia & Guerbouj, 2020). ZIS encourages the consumption of poor Muslim communities and creates income equality (Ridlo et al, 2021). Besides that, according to (Alghina et al, 2019), ZIS can also be distributed as business capital to MSME actors through BAZNAS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research regarding the influence of Islamic social finance, such as ZIS on economic growth has been developed in many countries, such as Pakistan (Azam et al, 2014), Malaysia (Khasandy & Badrudin, 2019), eight selected Muslim countries (Jedidia & Guerbouj, 2020), and Indonesia (Alghina et al, 2019;Arwani & Wahdati, 2020;Athoillah, 2018;Munfaati & Noviarita, 2023;Putriani et al, 2020;Ridlo & Wardani, 2020;Ridlo et al, 2021;Ridwan & Pimada, 2019;Suhendar et al, 2022;Supratman & Asih, 2022;Suprayitno, 2020;Triyawan et al, 2022;Wardani & Al Arif, 2021). Most studies find that Islamic social financial instruments (e.g ZIS) have a positive and significant effect on economic growth, but on the other hand, Islamic social finance has no significant effect (Munfaati & Noviarita, 2023;Ridlo & Wardani, 2020).…”
Section: Islamic Social Finance and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…This research confirms Ledhem (2020) and Smaoui and Nechi (2017) who state that the development of Sukuk does not significantly affect economic growth. However, in contrast to Ridlo et al (2021) and Tan and Shafi (2021), the difference in results is most likely because the data used in the two studies only covers corporate Sukuk, while in this study a combination of corporate and state Sukuk is used. Sukuk is a source of funding for businesses looking to boost marketing, innovation, and productivity.…”
Section: Effect Of Sukuk Growth On Indonesia's Economic Growth In The...mentioning
confidence: 99%